Estrogen induces St6gal1 expression and increases IgG sialylation in mice and patients with rheumatoid arthritis: a potential explanation for the increased risk of rheumatoid arthritis in postmenopausal women - Engdahl, Cecilia; Bondt, Albert; Harre, Ulrike; Raufer, Jasmin; Pfeifle, Rene; Camponeschi, Alessandro; Wuhrer, Manfred; Seeling, Michaela; Martensson, Inga-Lill; Nimmerjahn, Falk; Krönke, Gerhard; Scherer, Hans U.; et al. (Arthritis Research & Therapy, 2018)
BACKGROUND: Rheumatoid arthritis (RA) preferentially affects women, with the peak incidence coinciding with estrogen decrease in menopause. Estrogen (E2) may therefore have intrinsic immune-regulatory properties that vanish with menopause. Fc sialylation is a crucial factor determining the inflammatory effector function of antibodies. We therefore analyzed whether E2 affects immunoglobulin G (IgG) sialylation. METHODS: Postmenopausal (ovariectomized) mice were immunized with ovalbumin and treated with E2 or vehicle. Total and ovalbumin-specific IgG concentrations, sialylation, and Fcγ receptor expression were analyzed. Postmenopausal women with RA receiving hormone replacement therapy, including E2, or no treatment were analyzed for IgG sialylation. Furthermore, effects of E2 on the expression of the sialylation enzyme β-galactoside α2,6-sialyltransferase 1 (St6Gal1) were studied in mouse and human antibody-producing cells. RESULTS: E2 treatment significantly increased Fc sialylation of total and ovalbumin-specific IgG in postmenopausal mice. Furthermore, E2 led to increased expression of inhibitory Fcγ receptor IIb on bone marrow leukocytes. Treatment with E2 also increased St6Gal1 expression in mouse and human antibody-producing cells, providing a mechanistic explanation for the increase in IgG-Fc sialylation. In postmenopausal women with RA, treatment with E2 significantly increased the Fc sialylation of IgG. CONCLUSIONS: E2 induces anti-inflammatory effector functions in IgG by inducing St6Gal1 expression in antibody-producing cells and by increasing Fc sialylation. These observations provide a mechanistic explanation for the increased risk of RA in conditions with low estrogen levels such as menopause.
EVALuna2:34145